Shotgun proteomics of extracellular matrix in late senescent human dermal fibroblasts reveals a down-regulated fibronectin-centered network - Kun Cho; Kyeong Eun Yang; Soo-Bin Nam; Song-I. Lee; Eui-Ju Yeo; Jong-Soon Choi (Journal of Analytical Science and Technology, 2022)
Abstract Extracellular matrix (ECM) proteins play a pivotal role in cell growth and differentiation. To characterize aged ECM proteins, we compared the proteomes by shotgun method of young (passage #15) and late senescent (passage #40) human dermal fibroblasts (HDFs) using SDS-PAGE coupled with LC–MS/MS. The relative abundance of identified proteins was determined using mol% of individual proteins as a semi-quantitative index. Fifteen ECM proteins including apolipoprotein B (APOB) and high-temperature requirement factor 1 (HTRA1) were up-regulated, whereas 50 proteins including fibronectin 1 (FN1) and vitronectin (VTN) were down-regulated in late senescent HDFs. The identified ECM proteins combined with plasma membrane were queried to construct the protein–protein interaction network using Ingenuity Pathways Analysis, resulting in a distinct FN1-centered network. Of differentially abundant ECM proteins in shotgun proteomics, the protein levels of FN1, VTN, APOB, and HTRA1 were verified by immunoblot analysis. The results suggest that the aging process in HDFs might be finally involved in the impaired FN1 regulatory ECM network combined with altered interaction of neighboring proteins. Shotgun proteomics of highly aged HDFs provides insight for further studies of late senescence-related alterations in ECM proteins.